COMPARISON OF FUZZY LOGIC METHODS OF MAMDANI AND SUGENO IN DETERMINING THE ELIGIBILITY VALUE OF KIP-KULIAH SCHOLARSHIP RECIPIENTS - Latuconsina, Umi Aulia Vasa; Leleury, Zeth Arthur; Tilukay, Meilin Imelda; Haumahu, Gabriella (Parameter: Jurnal Matematika, Statistika dan Terapannya, 2025)
The government through the KIP-Kuliah program provides educational assistance to students from underprivileged families who continue their education at university. Although this program aims to increase access to higher education, there are several problems in its implementation, such as inaccuracy in determining the eligibility of scholarship recipients. This study aims to determine and compare the eligibility of KIP-Kuliah scholarship recipients in the UNPATTI Mathematics Study Program using the Fuzzy logic method of Mamdani and Sugeno, which considers factors such as parental dependents, parental income, and diploma grades. The calculation results show that the level of accuracy of the Mamdani method is 75.64% and the Sugeno method is 95.15%. Based on these results, it can be concluded that the Sugeno method provides a better level of accuracy than the Mamdani method in determining the eligibility of KIP-Kuliah scholarship recipients in the UNPATTI Mathematics Study Program.